Spoken Word Recognition Using Slantlet Transform and Dynamic Time Warping - Abou-Loukh, Sadiq J.; Gatea, Samah Mutasher (Nahrain University College of Engineering Journal, 2011)
Speech recognition system has been widely used by many researchers using different methods to fulfill a fast and accurate system. Speech signal recognition is a typical classification problem, which generally includes two main parts: feature extraction and classification. In this work, three feature extraction methods, namely SLT, DWT Db1 and DWT Db4, were compared. The dynamic time warping (DTW) algorithm is used for recognition. Twenty three Arabic words were recorded fifteen different times in a studio by one speaker to form a database. The proposed system was evaluated using this database. The result shows recognition accuracy of 93.04%, 92.17% and 94.78% using DWT Db1, DWT Db4 and SLT respectively.